Non-pecuniary returns to higher education: the effect on smoking intensity in the UK - Alfonso Miranda; Massimiliano Bratti (Institute for the Study of Labor (IZA), 2006)
In this paper we investigate whether higher education (HE) produces non-pecuniary returns via a reduction in the consumption of health-damaging substances. In particular, the paper focuses on studying the smoking intensity of British individuals. We use data on current smokers from the 1970 British Cohort Study and estimate endogenous switching count models for cigarette consumption. Results show that HE is endogenous with smoking. Once endogeneity is controlled for, HE is found to have a higher negative effect on smoking than in models where it is treated as exogenous.
Keywords: C35; I12; I21; 330; endogenous switching; count data; higher education; smoking; UK